Between Biography and Ethnography - Jackson, Michael (Harvard theological review, 2008)
My point of departure in this essay is Davíd Carrasco's Convocation Address at the Harvard Divinity School in September 2006. Speaking of the borderlands between Mexico and the United States, Carrasco projects an image of a vexed and ambiguous zone that is not merely geographic or political; it defines an existential situation of being betwixt and between, of struggle and suffering, that Karl Jaspers sums up in the term Grenzsituationen (borders/limit situations). The frontier throws up images of borderline experiences, of a destabilized and transgressive consciousness in which “dreams, repressed memories, psychological transferences and associations” possess greater presence than they do in ordinary waking life, and religious experiences emerge from the unconscious like apparitions. This interplay between borderlands and borderline phenomena—between “the differences we have with others and the conflicts within ourselves” also finds expression in the work of Gloria Anzaldúa. “Mestiza consciousness,” she observes, may be identified with a “juncture … where phenomena collide.” This implies “a shock culture, a border culture, a third country” where migrants find themselves at the limits of what they can endure, border patrol agents are stretched beyond the limits of what they can control, and intellectuals find that orthodox ways of describing and analyzing the world do not do justice to the experiences involved.